ANALISIS PENGGUNAAN BAHASA SISWA SMA EDU GLOBAL SCHOOL MEDAN DI MEDIA SOSIAL - Syahputra, Rahmat Ramadhan; Kartolo, Rahmat (Jurnal Bahastra, 2023)
A language is a communication tool used in everyday life, including in social media, without using language, communication will not work properly. The use of language in social media is interesting because it can be observed as related to sentence structure which refers to syntax, morphology, semantics, phonology, and pragmatics. Therefore, the purpose of this research is to find out students' use of language on social media in terms of grammar and language variations. The research conducted is a descriptive analysis that will provide an overview of the phenomena studied with a qualitative approach based on observations of students' use of language on social media. The sample used in this study were 4 students of class X SMA Edu Global School who have accounts on Instagram and WhatsApp social media. The selection of this sample was done randomly. The instruments used were observation sheets for grammatical errors and observation sheets for language variations. The data collected was then analyzed descriptively to show an overview of students' use of grammar and language variations in social media. The results of observations on students' use of language on social media, it can be concluded that there are errors in the use of student grammar on social media, for example, errors in writing words and phrases, errors in the use of punctuation marks such as periods, errors in the concept of repeating words, rarely or never using capitalize the initial letters and use abbreviations for a word or errors in writing/typing. In addition, there are three language variations used by students on social media, namely: language variations between Indonesian and English, local languages, and slang; the use of non-formal language caused by using word abbreviations; and language variations caused by using forms of expression/onomatopoeia.Language is a communication tool used in everyday life, including in social media, without using language, communication will not work properly. The use of language in social media is interesting because it can be observed as related to sentence structure which refers to syntax, morphology, semantics, phonology and pragmatics. Therefore, the purpose of this research is to find out students' use of language on social media in terms of grammar and language variations. The research conducted is a descriptive analysis which will provide an overview of the phenomena studied with a qualitative approach based on observations of students' use of language on social media. The sample used in this study were 4 students of class X SMA Edu Global School who have accounts on Instagram and WhatsApp social media. The selection of this sample was done randomly. The instruments used were observation sheets for grammatical errors and observation sheets for language variations. The data collected was then analyzed descriptively to show an overview of students' use of grammar and language variations in social media. The results of observations on students' use of language on social media, it can be concluded that there are errors in the use of student grammar on social media, for example errors in writing words and phrases, errors in the use of punctuation marks such as periods, errors in the concept of repeating words, rarely or never using capitalize the initial letters and use abbreviations for a word or errors in writing/typing. In addition, there are three language variations used by students on social media, namely: language variations between Indonesian and English, local languages, and slang; the use of non-formal language caused by using word abbreviations; and language variations caused by using forms of expression/onomatopoeia.